(untitled) (Iraqi Journal of Civil Engineering, 2021)
The most concerning issue confronting the planet these days is the ascent in Carbon dioxide (CO2) levels to record levels. The cement industries are answerable to between 6-8 % of worldwide CO2 emitting. In construction sectors, researchers tried to contribute in decreasing of CO2 in atmosphere produced by industry and using that was released in air. Accelerated CO2 curing is one of the methods used to get benefit from CO2 in the air. In this paper, CO2 concentration in addition to pressure, relative humidity and period of curing all had a significant influence upon the features of Cement – Based Composites. Results showed that using CO2 curing with different and specific properties of fibers (types, quantities, circumstances and lengths) improved the most mechanical properties and enhanced durability such as: strength, stiffness, ductility, toughness, porosity, and absorption.